2005
DOI: 10.1088/0953-8984/17/27/l01
|View full text |Cite
|
Sign up to set email alerts
|

On the abundance and general nature of the liquid–liquid phase transition in molecular systems

Abstract: Even a single-component liquid may have more than two kinds of isotropic liquid states. The transition between these different states is called a liquidliquid transition (LLT). An LLT has been considered to be a rather rare phenomenon, in particular for molecular liquids. Very recently, however, we found an LLT in triphenyl phosphite, which may be the first experimental observation of an LLT for molecular liquids. Here we report convincing evidence of the second example of LLT for another molecular liquid, n-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
108
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 27 publications
8
108
0
Order By: Relevance
“…Each scenario captures a certain feature of the glacial phase, but fails in explaining all of the experimental results in a consistent manner. Similar situations are often seen in other candidates of LLTs, such as l-butanol [LLT (13) vs. microcrystallization (40)(41)(42)(43)], confined water [LLT (5) vs. other phenomena (44)(45)(46)], and aqueous solutions [LLT (6, 7) vs. microcrystallization (8,28,47,48)]. For TPP, however, some pieces of experimental evidence supportive of the LLT scenario rather than the microcrystallization scenario have recently been reported (11,12).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Each scenario captures a certain feature of the glacial phase, but fails in explaining all of the experimental results in a consistent manner. Similar situations are often seen in other candidates of LLTs, such as l-butanol [LLT (13) vs. microcrystallization (40)(41)(42)(43)], confined water [LLT (5) vs. other phenomena (44)(45)(46)], and aqueous solutions [LLT (6, 7) vs. microcrystallization (8,28,47,48)]. For TPP, however, some pieces of experimental evidence supportive of the LLT scenario rather than the microcrystallization scenario have recently been reported (11,12).…”
supporting
confidence: 54%
“…This means that there can be more than two liquid states for a single-component substance. Despite its counterintuitive nature, there have recently been many pieces of experimental and numerical evidence for the existence of LLT, for various liquids such as water (1)(2)(3)(4)(5), aqueous solutions (6)(7)(8), triphenyl phosphite (9-12), l-butanol (13), phosphorus (14), silicon (15,16), germanium (17), and Y 2 O 3 -Al 2 O 3 (18,19). This suggests that the LLT may be rather universally observed for various types of liquids.…”
mentioning
confidence: 99%
“…It is a puzzle that there are so few cases of systems with liquid-liquid transitions above T g . Kurita and Tanaka [72] have shown that Kivelson's "glacial phase" of tri-phenyl phosphite, TPP is such a case and anticipate [73], as do we [48], that there should be many others but have so far only identified t-butanol as additional. The LL transition for TPP is indeed associated with rapid crystallization, as is the case with other polyamorphic transitions [22,24].…”
Section: Excess Heat Capacity Behavior Across the Broad Spectrum Of Gmentioning
confidence: 73%
“…We note that glass polymorphism is not particular to water. Experiments indicate that other materials, such as silicon, 57,58 germanium, 59, 60 silica, 61 aluminium-oxide yitrium-oxide mixtures, 62 n-butanol, 63,64 triphenyl phosphite, 65,66 and water-glycerol solutions, 67 also exhibit glass polymorphism, with low and high-density amorphous forms. Hence, characterizing water glass polymorphism may help to understand polyamorphism in other substances as well.…”
Section: Introductionmentioning
confidence: 99%